Penerapan Sosial Media dalam Strategi Meningkatkan Nilai Dakwah - Efendi, Erwan; Arsyad, Agam; Zein, Gilang Hardian; Auliadi, Rusdi; Fitra, Muhammad Aidil (IAI Nasional Laa Roiba Bogor, 2024)
The research has the theme about the application of social media in strategies to increase the value of da'wah. The aim of this research is to explain the role of social media in improving the quality of da'wah services to the public. Social media is expected to become a platform that can increase the value of da'wah and promote the face of Islam to diverse audiences. To maximize strategies in realizing the ideals of da'wah, a preacher is able to position himself towards audiences from various circles. Almost all da'wah now relies on social media as a strategy to increase the value of da'wah.